Impaired Postural Control and Altered Sensory Organization During Quiet Stance Following Neurotoxic Chemotherapy: A Preliminary Study - Scott M. Monfort PhD; Xueliang Pan PhD; Charles L. Loprinzi MD; Maryam B. Lustberg MD, MPH; Ajit M. W. Chaudhari PhD (Integrative Cancer Therapies, 2019)
Individuals diagnosed with chemotherapy-induced peripheral neuropathy (CIPN) demonstrate impaired balance and carry an increased risk of falling. However, prior investigations of postural instability have only compared these individuals against healthy controls, limiting the understanding of impairments associated with CIPN. Therefore, the purpose of this study was to better isolate postural control impairments that are associated with CIPN. Twenty cancer survivors previously diagnosed with breast or colorectal cancer participated. Participants were separated into 3 groups: no prior chemotherapy exposure (CON, n = 6), and recent treatment with taxane- or oxaliplatin-based chemotherapy with no/mild symptoms of CIPN (−CIPN, n = 8) or moderate/severe symptoms of CIPN (+CIPN, n = 6). Postural control was assessed by measuring center of pressure during standing balance conditions that systematically interfered with somatosensory, visual, and/or vestibular information. The presence of CIPN sensory symptoms was associated with impaired postural control, particularly during eyes-closed balance conditions ( P < .05). Additionally, medial-lateral postural instability was more pronounced in the +CIPN group compared with the −CIPN group and CON participants ( P < .05). Greater postural instability during eyes-closed balance in individuals with CIPN is consistent with impaired peripheral sensation. Balance impairments in cancer survivors with CIPN demonstrate the unique challenges in this population and motivate the need for targeted efforts to mitigate postural control deficits that have previously been associated with fall risk.